2015
DOI: 10.3109/00207454.2015.1079710
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chromosome 12p13 variants on ischemic stroke risk

Abstract: These findings indicate that rs12425791 G>A polymorphism may be a low-penetrance susceptibility marker of stroke in Asian populations and further studies are warranted to verify this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Regarding the rs11833579, some authors reported that the AA genotype increased the risk of IS [18, 29], while some authors reported an absence of association with IS [20, 2325, 30]. Consistent with the null results, in this study, we failed to find any association of the rs11833579 with IS risk.…”
Section: Discussionsupporting
confidence: 83%
“…Regarding the rs11833579, some authors reported that the AA genotype increased the risk of IS [18, 29], while some authors reported an absence of association with IS [20, 2325, 30]. Consistent with the null results, in this study, we failed to find any association of the rs11833579 with IS risk.…”
Section: Discussionsupporting
confidence: 83%
“…The first to be reported was an association with the chr12p13 locus, near NINJ2 , associated with incident stroke and ischemic stroke in particular in prospective population-based cohort studies participating in the CHARGE consortium [34]. However, although the same association was reported in several Asian studies [60], it could not be replicated in a large hospital-based genetic association study of prevalent stroke in European populations [61]. One potential explanation for these discrepant results, beside type I error (false positive finding), is that the chr12p13 locus could be associated with stroke severity and mortality more than with stroke risk.…”
Section: Role Of Genetic Risk Factors In Common Multifactorial Strokementioning
confidence: 94%
“…NINJ2 is a cell surface adhesion protein that is upregulated after nerve injury [16]. NINJ2 play an important role in nerve, stroke and inflammation [17][18][19][20]. We explored the effects of NINJ2 [21].…”
Section: Discussionmentioning
confidence: 99%